Evaluation of Toxic Stress of Copper Sulphate and Lead Nitrate on Hematological and Serum Biochemical Characteristics of Freshwater Cyprinid (Labeo rohita) (International Journal of Current Engineering and Technology, 2014)
L. rohita, the common freshwater cyprinid in Pakistan, is currently living in such habitats that are contaminated with heavy metals. Copper and lead metals are considered as the strong aquatic pollutants in this area. The aim of the study was to determine 96h LC50 values of copper sulphate [CuSO4.5H2O] and lead nitrate [Pb(NO3)2] for L. rohita and also to demonstrate the effects of their acute concentrations on hematology and serum biochemistry of the candidate fish. The 96h LC50 values for [CuSO4.5H2O] and [Pb(NO3)2] were found to be 3.15 mg/L and 6.80 mg/L respectively. Based on LC50 values, the experiments were conducted for 96h at acute concentrations of [CuSO4.5H2O] and [Pb(NO3)2] and data revealed a significant decrease (P
Keywords: Labeo rohita; Copper sulphate; Lead nitrate; Hematology; Serum biochemistry.